Ontogeny of a New Species of the Cambrian Series 3 (Middle Cambrian) Trilobite Genus Liostracina Monke, 1903 from North China and the Taxonomic Position of the Superfamily Trinucleoidea. (March 2014) - Park, Tae-Yoon S.; Kihm, Ji-Hoon; Kang, Imseong; Choi, Duck K.
Abstract : The Order Asaphida was grouped by the presence of a ventral median suture and a globular protaspis. The Superfamily Trinucleoidea has been assigned to the Order Asaphida, based on the recognition of a globular protaspis in the Ordovician representatives of the group, and the presence of a ventral median suture in the middle Cambrian genus Liostracina which has been regarded as a primitive sister-group to the post-Cambrian trinucleoideans. Recent studies demonstrate that the ventral median suture and the globular protaspis could have evolved multiple times in the trilobite evolutionary history, casting doubt on the traditional concept of the Order Asaphida. Inclusion of the Trinucleoidea into the Order Asaphida, therefore, has to be tested. It has recently been revealed that Liostracina simesi Jago and Cooper, 2005 did not possess a ventral median suture, implying that there could have been variable types of ventral suture within the genus Liostracina . Here we report the ontogeny of Liostracina tangwangzhaiensis n. sp. from the Cambrian Series 3 (middle Cambrian) strata of Shandong Province of North China. The material for this study includes protaspides, which are of flat, benthic morphology, contrasting to the globular protaspid morphology of the Ordovician trinucleoideans. The benthic protaspid morphology of L. tangwangzhaiensis indicates an independent evolution of the globular protaspis within the Superfamily Trinucleoidea. Together with the variable types of ventral suture within the genus Liostracina, the benthic protaspid morphology of Liostracina leads us to propose that the Superfamily Trinucleoidea be excluded from the Order Asaphida.